Water Permeability Characteristics of Normal Strength Concrete Made from Crushed Clay Bricks as Coarse Aggregate - Syed Ishtiaq Ahmad; Mohammad Anwar Hossain (Advances in Materials Science and Engineering)
Water permeability characteristic of concrete made from crushed clay bricks as coarse aggregate is investigated and compared with concrete made from natural stone aggregate. For this, six different brick and five different natural stone samples were selected. Crushing strength of brick samples and water absorption of aggregate produced from them were also measured. Concrete samples of three different compressive strengths were prepared as per ACI mix design method from each of these aggregate samples. Compressive strength of concrete that could be achieved with brick aggregate varied between 19 and 28 MPa, whereas, for stone aggregate, compressive strength varied between 24 and 46 MPa. These samples were then tested for water permeability using the AT 315 machine as per EN 12390-8: “Depth of Penetration of Water under Pressure.” Experimental results and subsequent analysis indicate that water permeability of brick aggregate concrete is 225% to 550% higher than that of concrete made from natural stone aggregate of identical compressive strength. Water permeability was found to be directly related to compressive strength, water absorption, and porosity of hardened concrete. It was also observed that water permeability of concrete is influenced by water absorption of brick aggregate and crushing strength of brick.